Large animal evaluation of riboflavin and ultraviolet light–treated whole blood transfusion in a diffuse, nonsurgical bleeding porcine model. Issue 3 (13th January 2015) - Okoye, Obi T.; Reddy, Heather; Wong, Monica D.; Doane, Suzann; Resnick, Shelby; Karamanos, Efstathios; Skiada, Dimitra; Goodrich, Raymond; Inaba, Kenji
<x xml:space="preserve">Abstract</x> Background The Mirasol system has been demonstrated to effectively inactivate white blood cells (WBCs) and reduce pathogens in whole blood in vitro. The purpose of this study was to compare the safety and efficacy of Mirasol‐treated fresh whole blood (FWB) to untreated FWB in an in vivo model of surgical bleeding. Study Design and Methods A total of 18 anesthetized pigs (40 kg) underwent a 35% total blood volume bleed, cooling to 33°C, and a standardized liver injury. Animals were then randomly assigned to resuscitation with either Mirasol‐treated or untreated FWB, and intraoperative blood loss was measured. After abdominal closure, the animals were observed for 14 days, after which the animals were euthanized and tissues were obtained for histopathologic examination. Mortality, tissue near‐infrared spectroscopy, red blood cell (RBC) variables, platelets (PLTs), WBCs, and coagulation indices were analyzed. Results Total intraoperative blood loss was similar in test and control arms (8.3 ± 3.2 mL/kg vs. 7.7 ± 3.9 mL/kg, p = 0.720). All animals survived to Day 14. Trended values over time did not show significant differences—tissue oxygenation (p = 0.605), hemoglobin (p = 0.461), PLTs (p = 0.807), WBCs (p = 0.435), prothrombin time (p = 0.655), activated partial thromboplastin time (p = 0.416), thromboelastography (TEG)–reaction time (p = 0.265), or TEG–clot formation time (p = 0.081). Histopathology did not show significant differences between arms. Conclusions Mirasol‐treated FWB did not impact survival, blood loss, tissue oxygen delivery, RBC indices, or coagulation variables in a standardized liver injury model. These data suggest that Mirasol‐treated FWB is both safe and efficacious in vivo.